2012
DOI: 10.1186/1471-2229-12-195
|View full text |Cite
|
Sign up to set email alerts
|

Plant plasma membrane-bound staphylococcal-like DNases as a novel class of eukaryotic nucleases

Abstract: BackgroundThe activity of degradative nucleases responsible for genomic DNA digestion has been observed in all kingdoms of life. It is believed that the main function of DNA degradation occurring during plant programmed cell death is redistribution of nucleic acid derived products such as nitrogen, phosphorus and nucleotide bases. Plant degradative nucleases that have been studied so far belong mainly to the S1-type family and were identified in cellular compartments containing nucleic acids or in the organell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Arabidopsis CAN1 and CAN2 nucleases are neutral, Ca 2+ -dependent nucleases displaying different specificities toward single-stranded DNA, double-stranded DNA, and RNA substrates. 53) In this study, we showed that IREN activity is slightly activated in the presence of Ca 2+ or in the presence of Mg 2+ /Mn 2+ , but is strongly activated in the presence of both Ca 2+ and Mg 2+ . In addition, IREN was inhibited by Zn 2+ and degraded both single-stranded and double-stranded DNA (data not shown).…”
Section: Discussionsupporting
confidence: 47%
“…Arabidopsis CAN1 and CAN2 nucleases are neutral, Ca 2+ -dependent nucleases displaying different specificities toward single-stranded DNA, double-stranded DNA, and RNA substrates. 53) In this study, we showed that IREN activity is slightly activated in the presence of Ca 2+ or in the presence of Mg 2+ /Mn 2+ , but is strongly activated in the presence of both Ca 2+ and Mg 2+ . In addition, IREN was inhibited by Zn 2+ and degraded both single-stranded and double-stranded DNA (data not shown).…”
Section: Discussionsupporting
confidence: 47%
“…N‐myristoylated and S‐acylated proteins include well‐known proteins such as many of the calcium‐dependent protein kinases (CPKs; Martin & Busconi, ) and calcineurin‐B like proteins (CBLs; Batistic et al ., ), the heterotrimeric G‐protein α‐subunit GPA1 (Adjobo‐Hermans et al ., ), receptor‐like cytoplasmic kinases (Hemsley et al ., ; Liu et al ., ) and more unexpected groups of proteins such as group 3 h ‐Thioredoxins ( h ‐TRX; Hemsley et al ., ; Traverso et al ., ). An entirely novel class of Ca 2+ ‐dependent nucleases typified by the CAN1 and CAN2 proteins of Arabidopsis has been proposed to be N‐myristoylated and S‐acylated (Lesniewicz et al ., ), a finding that was subsequently confirmed for S‐acylation (Hemsley et al ., ). These nucleases are found at the PM, an entirely unique localisation for this class of proteins, although the importance of this localisation in their function has yet to be described (Lesniewicz et al ., ).…”
Section: Types Of Lipid Modificationmentioning
confidence: 54%
“…An entirely novel class of Ca 2+ ‐dependent nucleases typified by the CAN1 and CAN2 proteins of Arabidopsis has been proposed to be N‐myristoylated and S‐acylated (Lesniewicz et al ., ), a finding that was subsequently confirmed for S‐acylation (Hemsley et al ., ). These nucleases are found at the PM, an entirely unique localisation for this class of proteins, although the importance of this localisation in their function has yet to be described (Lesniewicz et al ., ). Interestingly, some bacterial type‐III secreted effector proteins are N‐myristoylated and S‐acylated once inside the host cell by the host machinery.…”
Section: Types Of Lipid Modificationmentioning
confidence: 54%
“…In recent years S-acylation in plants has begun to come of age with the enzymes responsible for S-acylation being identified and characterized, [2][3][4] in-depth analysis of the role of S-acylation in the function of ROP GTPases, 5-8 many other S-acylated proteins recently being described [9][10][11][12] and tools to analyze S-acylation being developed. 7,13 Despite the important properties of S-acylation and increased interest in its function, it is still very difficult to predict whether a protein is S-acylated.…”
Section: Palmitoylation In Plantsmentioning
confidence: 99%